Tarte Cottage / Ahmad Nawawi Muhamad ... [et al.] - Muhamad, Ahmad Nawawi; Masri, Ahmad Safarin; Samsulbahri, Mohd Shahrizan; Zamri @ Zimri, Mohd Taufik; Mohd Diah, Tajul Fitri (Faculty of Hotel and Tourism Management, 2006)
Tarte Cottage is the upcoming bakery house which has a good and bright potential as well as welcoming bright future in food industry generally, pastries making specifically. As the name sounds, Tarte Cottage is specialized in offering home made and freshly oven bake of variety delightful tarts. Going beyond that, Tarte Cottage also offers unique pastries and cakes. To fulfill customer needs and demands, Tarte Cottage always welcome any requisition to supply pastry products for parties and anniversaries.